Sistem Informasi Pencegahan Dan Penanggulangan Stunting Berbasis WEB - Dani Yusuf; Prima Dina Atika; Rejeki, Sri (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
This paper discusses the design of a stunting information system starting from creating a posyandu schedule to following up on stunted children. This system is built on a web basis so that it can be accessed by agencies related to stunting management and the public who want to see stunting activities in the city area. Bekasi. The system development method used is a prototype with the aim of accelerating the system development process so that this application can be used quickly and precisely according to the needs of its users. The result of the design and manufacture of this application is software that is expected to facilitate the implementation of activities for handling and overcoming stunting children through fast and accurate data collection.